Pengaruh Modul Ajar Ipas pada Materi Cerita di Daerah Tempat Tinggalku Terhadap Hasil Belajar Siswa Kelas IV di SDN Lebakrejo IV Purwodadi - Kumala Dewi Pertiwi; Oktaviani Adhi Suciptaningsih (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This study aims to examine the effect of the science and social studies module on story material in the area where I live on the learning outcomes of IV grade students at SDN Lebakrejo IV Purwodadi. This type of research is quantitative using experimental research methods, the form of Quasi Experimental Design research and the design of this research, namely Nonequivalent Control Group Design. The instrument used in this research is the test instrument. The population in this study amounted to 27 students. The instrument includes a pre-test and post-test using the t-test statistical analysis technique. The results showed that there was a significant influence from the use of the science teaching modules which had been developed according to the needs and characteristics of students, namely the t count (3.52) was greater than the t table (2.06), so it could be concluded that the difference between the mean post-test scores of the two groups were statistically significant.